2020
DOI: 10.20945/2359-3997000000281
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D deficiency in exclusively breastfed infants at a tertiary healthcare facility in Nairobi, Kenya

Abstract: Objective: To determine the prevalence of vitamin D deficiency (VDD) in exclusively breastfed infants at the Aga Khan University Hospital Nairobi, Kenya (AKUHN). The relationships between 25-hydroxyvitamin D; 25OHD, parathyroid hormone (PTH), maternal vitamin D supplementation, and sunlight exposure were also determined. Subjects and methods: Blood from 98 infants was assayed for 25OHD, calcium, phosphate, and PTH. Socio-demographic and clinical characteristics were analyzed using descriptive statistics and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
(21 reference statements)
2
5
1
Order By: Relevance
“…The prevalence of vitamin D insufficiency or deficiency among infants in tropical countries was previously expected to be low because of the large amount of sunlight in these areas. The prevalence of vitamin D insufficiency and deficiency (≤20 ng/mL) among unsupplemented breastfed infants in the present study are comparable with those reported in Hong Kong (60%) [ 13 ], but lower than those reported in India (90%) [ 14 ], Taiwan (86.1%) [ 15 ], Qatar (83%) [ 16 ], and Japan (76.9%) [ 17 ] but higher than those in Boston, MA, USA (40%) [ 18 ], Kenya (23.4%) [ 19 ], and Indonesia (16.7%) [ 20 ]. The variation in these reported prevalences was likely caused by multiple factors, such as the infants’ age, ethnicity, geographical location, and study methodology.…”
Section: Discussionsupporting
confidence: 79%
“…The prevalence of vitamin D insufficiency or deficiency among infants in tropical countries was previously expected to be low because of the large amount of sunlight in these areas. The prevalence of vitamin D insufficiency and deficiency (≤20 ng/mL) among unsupplemented breastfed infants in the present study are comparable with those reported in Hong Kong (60%) [ 13 ], but lower than those reported in India (90%) [ 14 ], Taiwan (86.1%) [ 15 ], Qatar (83%) [ 16 ], and Japan (76.9%) [ 17 ] but higher than those in Boston, MA, USA (40%) [ 18 ], Kenya (23.4%) [ 19 ], and Indonesia (16.7%) [ 20 ]. The variation in these reported prevalences was likely caused by multiple factors, such as the infants’ age, ethnicity, geographical location, and study methodology.…”
Section: Discussionsupporting
confidence: 79%
“…The prevalences of vitamin D insu ciency and de ciency (≤ 20 ng/mL) among unsupplemented breastfed infants in the present study are comparable with those reported in Hong Kong (60%) (13). The prevalences were lower than those reported in India (90%) (14), Taiwan (86.1%) (15), Qatar (83%) (16), and Japan (76.9%) (17) but higher than those in Boston, MA, USA (40%) (18), Kenya (23.4%) (19), and Indonesia (16.7%) (20). The variation in these reported prevalences was likely caused by multiple factors, such as the infants' age, ethnicity, geographical location, and study methodology.…”
Section: Discussionmentioning
confidence: 56%
“…The prevalence obtained in our study is similar to other studies carried out in near by regions (Dar es Salaam) Tanzania and (Nairobi) Kenya. This can be explained by the fact that they had similar study population, similar weather characteristics and socioeconomic status (4,13). The prevalence of Vitamin D de ciency among infants was ranging from 21.2% to 83.7% in various studies done in East Africa (4,5,13,14).…”
Section: Discussionmentioning
confidence: 89%
“…Younger infants appeared more likely to have Vitamin D de ciency and may be explained by signi cant number of them being exclusively breastfed (17). Breast milk has low level of vitamin D yet mothers in Arusha are not supplemented with Vitamin D and plausibly they could also be low in Vitamin D. Said N et al made similar observations associating vitamin D de ciency with age less than six month and exclusive breastfeeding (13).…”
Section: Discussionmentioning
confidence: 91%